PENGEMBANGAN MEDIA BELAJAR MONOPOLI MATEMATIKA BUDAYA (MONOMABA) BERBASIS BUDAYA DI SALATIGA UNTUK MENINGKATKAN KEMAMPUAN PROBLEM SOLVING DAN RASA CINTA BUDAYA PADA PEMBELAJARAN PERKALIAN MATEMATIKA SISWA KELAS IV SD - Nugraha, Ronan Beema; Kusuma, Dani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve problem-solving abilities and love of culture. This type of research is development research (Research & Development). The subjects in this research were 16 students in class IV-A at SDN Blotongan 02. Data collection was carried out by interviews, observations, and initial ability tests. This research method uses quantitative descriptive. The research results show that Monomaba media can be an alternative for fourth grade teachers to improve students' problem solving abilities and love of culture. The results of the practicality sheet analysis show a percentage of 81.5%, which means it is included in the good category. Media Monomaba obtained a material expert validation score of 90.6 and a media expert validation score of 94.6. Both validation results are in the